An Analysis on the Use of Social Media Platforms to Enhancing Writing Skills Among Higher Education Students in University of Mataram - Khumairah, Azahra; Thohir, Lalu; Zamzam, Ahmad (Program Studi Magister Pendidikan IPA, Universitas Mataram, 2025)
Writing skills include improving critical thinking skills, deepening understanding of material, developing communication skills, and improving overall self-esteem. Writing helps to hone their analytical, synthesizing, and evaluating skills, and trains them to convey ideas systematically and effectively. The research aimed to explore students' experiences and attitudes towards learning to employ social media websites as tools for developing their writing skills with particular focus on vocabulary enhancement, coherence, and grammaticality. This research used a case study design, the student’s perception of social media utilization was obtained by using a set of questionnaires and interviews. Qualitative research method was adopted, and purposive sampling was utilized to enlist 15 undergraduate students who were actively using social media for writing-related activities. This research specifically analyzes the role of social media platforms such as Twitter/X, Facebook, YouTube, and TikTok as tools to support students in enhancing their English proficiency, particularly in writing. The data analysis followed the interactive model involving the three main stages : data reduction, data display, and verification. The findings revealed that the students actively used social media platforms to enhance their writing in English. The high frequency of social media used, with 53.3% of students spending more than three hours daily on these platforms primarily for learning purposes, demonstrates the observational learning process in action. This research reveals positive perspective towards the use of social media, distinct platform preferences that align with different aspects of the theoretical framework. Instagram emerges as the most popular platform (40%), followed by Twitter/X (26.7%), TikTok (13.3%), and Facebook (13.3%). The students frequently use platforms such as Instagram, Twitter/X, TikTok, and Facebook for writing-related activities. Instagram was the most commonly used platform, followed by Twitter/X. These platforms are preferred because of their interactive and visual nature, which provides opportunities for both creative expression and peer engagement